The Effect of Customer Expectations, Perceived Value, and Patient Experience on BPJS Patient Satisfaction: The Role of Trust and Social Media Usage - Novi Asiye; lilik Wahyudi (Eduvest - Journal of Universal Studies, 2025)
Indonesia’s national health insurance program (Jaminan Kesehatan Nasional/JKN), managed by BPJS Kesehatan, has achieved near-universal coverage with over 276 million participants as of 2024, representing 98.19% of the population. Despite this quantitative success, qualitative challenges persist in achieving satisfactory healthcare experiences, particularly in hospitals primarily serving BPJS patients. Common concerns include long waiting times, complex administrative procedures, service disparities compared to private-pay patients, and limited access to specialists. This study investigates how customer expectations, patient experience, and perceived value influence patient satisfaction among BPJS participants at RS Indriati Solo Baru. It also examines trust as a mediating variable and social media usage as a moderating factor. Using a quantitative approach with Structural Equation Modeling (SmartPLS), data from 340 BPJS patients were analyzed. Findings reveal that customer expectations significantly affect both experience and satisfaction, while patient experience positively influences trust and satisfaction. Perceived value has a strong impact on trust and satisfaction, and trust mediates the relationship between experience and satisfaction. Social media usage directly affects satisfaction, though its moderating role is unsupported. These results validate Expectation Confirmation Theory, SERVQUAL, and trust-based frameworks within Indonesia’s health insurance system, offering insights for enhancing service quality, digital engagement, and patient-centered care.